Improvement of dried red bell pepper dices - Manalo, Maria Teresa J.; Guzman, Matilde P. (1982.)
Cabinet-dried and solar-dried red bell pepper dices were compared for their physico-chemical and sensory characteristics. Their preferred product was then compared with the commercial sample. Microbiological examination of the preferred product was done. Results show that cabinet-drying of red bell pepper dices produces a more acceptable product than solar-drying. Deteriorative changes in color and odor occur due to the 10 hour drying time and the unstable drying conditions involved. Darkening of color and the loss of the characteristic bell pepper odor are directly proportional to the drying time. It is also correlated to the high carotenoid and fat content of the pepper. Oxidation of the poly-unsaturated fatty acids and carotene occurs when sundrying. Flavor, however, is not greatly affected by the drying process since these are mostly non-volatile oleoresinous compounds. The cabinet-dried product was more acceptable than the commercial sample. It had a lower moisture content than the latter. Aside from this, cabinet-drying retained most of the quality characteristics of the bell pepper. The commercial sample lacked the eye appeal of the fresh bell pepper. Since moisture content is low, the cabinet-dried sample has a higher rehydration capacity. Microbiological examination of the cabinet-dried sample shows a proliferation of molds. Gram + and Gram - rods and cocci, respectively, were observed to contaminate the product.
Thesis (BSFT)--University of the Philippines Diliman
Keywords: Peppers, Dried